RANCANG BANGUN SISTEM INFORMASI STOK BERAS DI GUDANG BULOG TEGALGIRANG - Hilman Prayitno; Fhaisal Anwar; Dede Abdurahman (Universitas Muhammadiyah Tangerang, 2019)
Perum Bulog is needed as a buffer for rice reserves so that it can be used when the dry season arrives. The role of Bulog Public Corporation as a State-Owned Enterprise also carries the task of fulfilling the people's food rights, especially for Poor Households (RTM). From 2000 to 2007 the distribution of rice for the poor was an average of 1.6 million tons per year with the aim of approximately 7 to 10 million RTM with a 10 kg ceiling at 7 years RTM. (Sahdan, 2014). Designing an information system for rice stocks in the tegalgirang warehouse to record the income and expenditure of rice stocks in the warehouse, The purpose of this article is to apply computer science obtained from college and to gain experience in the real work environment Writing this article uses the method of developing Rapid Application Development (RAD) systems, in this method there are three phases in RAD that involve analysts and users in the stages of assessment, design, and implementation. Keywords: Rice stock, Rice stock information system, RAD